PEMANFAATAN POTENSI SUMBER DAYA LOKAL SEBAGAI PENGEMBANGAN KETAHANAN PANGAN DI DESA BOTUMOPUTI KECAMATAN TIBAWA KABUPATEN GORONTALO PROVINSI GORONTALO - Saleh, Yanti; Tsamara, Devy; Astika, Lini (Universitas Negeri Gorontalo, 2023)
Through internships, we are required to practice science, technology, and art. We are expected to be motivators and facilitators of development efforts, especially in rural areas.Communities can share existing problems and find solutions with intern students so that cooperation is established in the development process in the local area. The purpose of this research is to provide understanding to the community and village apparatus about Utilizing the Potential of Local Resources in Botumoputi Village as a Food Security Village Development. Activities are carried out through training for the community, especially mothers to utilize corn which is a source of food security in the village. This activity was carried out to increase the selling value so that it was higher.Keywords: corn, utilization of potential local resources, food security